OPTIMIZING THE ROLE OF TEACHERS IN INSTILLING THE CHARACTER OF RESPONSIBILITY OF GRADE III STUDENTS OF MI ALAM YA BUNAYYA BUNGO - Nur Fadilah; Muhammad Solihin; Sopriyanto (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
This study aims to analyze the optimization of the role of teachers in instilling the character of responsibility in grade III students of MI Alam Ya Bunayya Bungo, identify the supporting and inhibiting factors, and explain the implications of the findings for the development of character education in madrasah ibtidaiyah. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation of school principals, grade III teachers, students, and parents/guardians of students. The results of the study show that the cultivation of a responsible character is carried out through the example of teachers, habituation of positive behavior, positive reinforcement, integration of values in learning, evaluation, and reflection, as well as contextual activities such as gardening, siroh stories, and group work. The novelty of this research lies in the integration between the pillars of natural school leadership, the Bloom approach, the supervision of the principal, the KKG forum, school-family communication, and real learning experiences as an ecosystem for the formation of responsibility. Implicitly, this research contributes to the strengthening of character education theory that emphasizes the integration of moral, affective, and behavioral aspects, while offering a practical model of responsibility coaching that is systematic, collaborative, contextual, and sustainable to be applied to Islamic basic education. These findings confirm that the success of character education does not rely enough on normative lectures, but rather requires teacher consistency, family support, school culture, and direct experience so that the value of responsibility is internalized in students’ daily behavior in a stronger and more meaningful way.